Osteopontin and latent‐TGF β binding‐protein 2 as potential diagnostic markers for HBV‐related hepatocellular carcinoma - Costa, Andre Nogueira; Plymoth, Amelie; Santos‐Silva, Daniela; Ortiz‐Cuaran, Sandra; Camey, Suzy; Guilloreau, Paule; Sangrajrang, Suleeporn; Khuhaprema, Thiravud; Mendy, Maimuna; Lesi, Olufunmilayo A.; Chang, Hee‐Kyung; Oh, Jin‐Kyoung; et al. (International journal of cancer, 2015)
Chronic Hepatitis B (HB) is the main risk factor for chronic liver disease (CLD) and hepatocellular carcinoma (HCC) in many low‐resource countries, where diagnosis is constrained by lack of clinical, histopathological and biomarker resources. We have used proteomics to detect plasma biomarkers that outperform α‐Fetoprotein (AFP), the most widely used biomarker for HCC diagnosis in low‐resource contexts. Deep‐plasma proteome analysis was performed in HCC patients, patients with CLD and in HB‐carrier controls from Thailand (South‐East Asia) and The Gambia (West‐Africa). Mass spectrometry profiling identified latent‐transforming growth factor β binding‐protein 2 (LTBP2) and Osteopontin (OPN) as being significantly elevated in HCC versus CLD and controls. These two proteins were further analyzed by ELISA in a total of 684 plasma samples, including 183 HCC, 274 CLD and 227 asymptomatic controls. When combined, LTBP2 and OPN showed an area under the receiver operating curve of 0.85 in distinguishing HCC from CLD in subjects with AFP <20 ng/mL. In a prospective cohort of 115 CLD patients from Korea, increased plasma levels of LTBP2 and/or OPN were detected in plasma collected over 2 years prior to diagnosis in 21 subjects who developed HCC. Thus, the combination of LTBP2 and OPN outperformed AFP for diagnosis and prediction of HCC and may therefore improve biomarker‐based detection of HBV‐related HCC. What's new? Chronic infection with hepatitis B virus (HBV) is the main risk factor for chronic liver disease and hepatocellular carcinoma (HCC) in many low‐resource countries, where diagnosis is constrained by lack of clinical, histopathological, and biomarker resources. Here, deep‐plasma proteomics was used to identify candidate biomarkers for HCC diagnosis. Validation studies on a total of 684 samples showed that elevated levels of LTBP2 and/or OPN are highly specific and sensitive markers for distinguishing HCC from chronic liver disease. LTBP2 appears highly associated with HBV‐related HCC, while OPN shows a robust and consistent association with HCC in both HBV and HCV contexts.